Academic Motivation of Students in Secondary Economic Education: Adaptation of the AMS - Andraž Konc (International Journal of Management, Knowledge and Learning, 2025)
Purpose: This study aims to examine differences in academic motivation among students in secondary economic education, focusing on gender differences, the relationship between motivation and academic performance, and the most prevalent types of motivation.